3D Interdigital Electrodes Dielectric Capacitor Array for Energy Storage Based on Through Glass Vias. Issue 8 (9th February 2022) - Fang, Zhen; Gao, Libin; Chen, Hongwei; Deng, Bowen; Jili, Xiaobing; Li, Wenlei; Liang, Tianpeng; Qu, Sheng; Chen, Yuzhe; Liang, Kexin; Zhang, Jihua
Abstract: Dielectric capacitors are ideal for high power pulse system due to their high‐power density. However, the traditional dielectric capacitor cannot achieve large capacitance density and combine with the high breakdown voltage. Through this research, the internal structure of photosensitive glass can be transformed into multilayer interdigital electrodes structure through photolithography and laser induced processes. It is realized through the transition from the 2D structure to the 3D interdigital electrodes dielectric capacitor. In this case, the specific surface area electrode structure presents exponential increase and dielectric layers thickness decrease, which provide a large capacitance density. The new 3D capacitors, via reducing the roughness of the electrode surface, a uniform porous inner wall improves the breakdown strength (8.15 MV cm −1, which is 2 times to photolithographic). As a result, these highly‐density regular electrodes array effectively improve the capacitance density to 48.5 nF cm −2, which is 422 times larger than that of planar structure. Moreover, the new 3D capacitors fabricated by laser‐induce exhibit smoother inner wall surface and more rounded shape of electrode holes, achieving very large energy storage density of ≈3.4 Wh kg −1 (14.688 J cm −3 ) and power density of ≈6.48 × 10 11 W kg −1 . Abstract : Using photosensitive glass to innovate 3D interdigital electrodes dielectric capacitor. Demonstrating the mechanism of laser induced in glass graphics, optimize the process of laser induced, and obtain high depth‐to‐diameter ratio nonthrough porous array. Studying the influence of the porous inner wall on the breakdown voltage, reduce the roughness and achieve the improvement of the breakdown strength and energy storage density.